Sosialisasi Undang Undang Cipta Kerja di Desa Kampung Tengah Kecamatan Pangkalan Jambu Kabupaten Merangin - Harmaini; Chandra, Febrian; Kusaimah; Susanti, Julia (PT. Meja Ilmiah Publikasi, 2024)
This community service aims to help the public become familiar with the rules of Law Number 11 of 2021 concerning Job Creation as well as introducing legal concepts in Law Number 11 of 2021 concerning Job Creation. The method used in this activity is in-depth discussion and a socio-cultural approach. The activity of Increasing the Role of Youth in Environmentaland Forestry Conservation in Kungkai Village, was achieved, attended by 33 people, by discussing the Job Creation Law, with the main discussion points of the benefits and objectives of the Law, scope, employment and mining with its initiation The omnibus law concept in the Job Creation Law in Indonesia is a reform regulation that is appropriate in its implementation and has a positive impact on the progress of the investment business climate for the realization of the welfare of the Indonesian people.